The Influence of Operational Costs And Operational Revenues (BOPO), Debt To Equity Ratio (DER), and Capital Adequacy Ratio (CAR) On Profitability In Banking Companies Listed On The Indonesia Stock Exchange (IDX) For The 2018-2023 Period - Fadhilah, Anisah Salma; Kusumawardhani, Ratih; Sari, Pristin Prima (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study investigates the influence of the Operational Costs to Operational Revenues Ratio (BOPO), Debt to Equity Ratio (DER), and Capital Adequacy Ratio (CAR) on the profitability of Indonesian banks listed on the Indonesia Stock Exchange (IDX) during the period from 2018 to 2023. Employing a quantitative approach and multiple linear regression analysis, the research reveals that BOPO has a significant negative impact on profitability, indicating that higher operational costs lead to diminished profitability. In contrast, both DER and CAR exhibit significant positive effects, highlighting that increased leverage and adequate capital can enhance profitability. The study applies purposive sampling, selecting 25 banks based on specific criteria, and relies on secondary data from financial reports. Classical assumption tests—such as normality, multicollinearity, autocorrelation, and heteroscedasticity—verify the reliability of the data. The findings demonstrate that BOPO, DER, and CAR collectively account for 45% of the variation in profitability, while the remaining 55% is attributed to external factors. These results align with previous studies emphasizing the critical roles of operational efficiency, leverage management, and capital adequacy in driving bank profitability. This study provides valuable insights for bank executives, investors, and policymakers, underscoring the importance of efficient cost control, balanced leverage, and sufficient capital to ensure financial stability and profitability within the banking sector.